Pengaruh Kompetensi Profesional dan Kompetensi Pedagogik Guru terhadap Pelaksanaan Kurikulum 2013 - Habibi Habibi (Departement of Mathematics Education, 2024)
This study aims to determine the influence between pedagogic competence and teacher professional competence on the implementation of the 2013 curriculum. This study used a multiple regression analysis with the population being the teacher council of SMPN as many as 30 people and MTsN as many as 35 people with a total of 65 people. The research instruments used were the Variable X1 questionnaire (Pedagogic Competence) of 30 questions that had been tested for validity and reliability, the Variable X2 questionnaire (Teacher Professional Competence) as many as 30 questions that had been tested for validity and reliability, and the Variable Y questionnaire (Implementation of the 2013 Curriculum) as many as 30 questions that had been tested for validity and reliability. The results showed the influence of pedagogic competence and professional competence of teachers on the implementation of the 2013 curriculum. From data processing, a double regression equation was obtained between Y = 6.315 + 0.391X1 + 0.377 X2, with a significant level of 0.05 obtained Ftable of 0.66. Because> which is 138.8 >0.66, then reject H0 and accept H1, thus there is an influence of professional competence and pedagogic competence of teachers on the implementation of the 2013 curriculum.